Locating Invisible Policies: Health Canada’s Evacuation Policy as a Case Study - Lawford, Karen (Atlantis)

(untitled) (Mount Saint Vincent University, 2016)
I describe an initial tool for revealing invisible policies. Invisible policies are made apparent by three criteria: allocation of resources, material impacts, and reactions. Allocation of resources can be economic, human, or otherwise. Material impacts are those that are tangible and can be described as having a physical impact in some manner. Finally, the reactions of those impacted by the policy, like agencies and scholars, provide a third lens through which these policies can be understood and identified. Using the three criteria, I reveal the long-standing “evacuation policy” as a genuine and authentic policy, which is currently applied to those First Nations populations falling under federal jurisdiction. My contribution to policy analysis is to provide another tool to close a gap in the literature with respect to the analysis of invisible policies.This paper won the Women’s and Gender Studies et Recherches Féministes (WGSRF) Graduate Essay Prize in 2014.